Servicing the public debt : the role of government’s behavior towards debt - Monteiro, Ricardo Oliveira Alves (2015)
This article presents a model in which haircuts on public debt may occur. My focus relies on the explanation and numerical exploration of multiple equilibria. Calvo (1988) first found multiple equilibrium interest rates due to investors’ self-fulfilling expectations of a partial default in a model with exogenous debt. I use Calvo’s (1988) setting to study the impact of endogenizing debt on multiplicity. This is a relevant exercise as in this setting the government has the ability to choose the optimal level of debt. More than that, if it behaves as a large agent it can influence the interest rate it will face. In particular, I find that if the interest rate schedule is presented as in Arellano (2008), depending on debt at maturity, uniqueness can be achieved by a government behaving as a large agent. However, investors can also coordinate on offering a schedule depending on the initial level of debt, as implicitly defined in Calvo (1988). In this case there is more than one equilibrium, provided that public expenditure in the first period is not extremely high.